2020
DOI: 10.3390/ijms21051811
|View full text |Cite
|
Sign up to set email alerts
|

Cell Fusion-Mediated Tissue Regeneration as an Inducer of Polyploidy and Aneuploidy

Abstract: The biological phenomenon of cell fusion plays a crucial role in several physiological processes, including wound healing and tissue regeneration. Here, it is assumed that bone marrow-derived stem cells (BMSCs) could adopt the specific properties of a different organ by cell fusion, thereby restoring organ function. Cell fusion first results in the production of bi- or multinucleated hybrid cells, which either remain as heterokaryons or undergo ploidy reduction/heterokaryon-to-synkaryon transition (HST), there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 123 publications
(273 reference statements)
0
25
0
3
Order By: Relevance
“…First of all, cell-cell fusion is a complex and tightly regulated process. Cells are not per se fusogenic, but have to enter a pro-fusogenic state first [1,4,6,7,9,77]. Likewise, hybridized cells have to return into a non-fusogenic state to prevent further uncontrolled fusion events.…”
Section: How Do Cancer Cells Fuse?mentioning
confidence: 99%
“…First of all, cell-cell fusion is a complex and tightly regulated process. Cells are not per se fusogenic, but have to enter a pro-fusogenic state first [1,4,6,7,9,77]. Likewise, hybridized cells have to return into a non-fusogenic state to prevent further uncontrolled fusion events.…”
Section: How Do Cancer Cells Fuse?mentioning
confidence: 99%
“…This transmission process has been widely described, notably in the fusion between cancer cells and leucocytes, where hybrid cells take advantage of the properties of the parents by inheriting both tumoral proliferation and leucocyte mobility properties, hence promoting metastatic dissemination 6 , 7 , 13 – 15 . Another consequence of cell–cell fusion is the acquisition of new properties which can be explained by the genomic and transcriptomic reshuffling that occurs in hybrid following a cell–cell fusion event 16 . Moreover, some studies have demonstrated that cell fusion can promote tumour initiation or participate in tumour relapse with the acquisition of drug resistance 6 , 17 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The biological phenomenon of cell fusion plays a crucial role in several physiological processes, including wound healing, tissue regeneration and tumor metastasis. 20 In recent years, 21 studies have shown that cell fusion can be spontaneous in the development of tumor. The fusion between tumor cells, as well as the fusion between tumor cells and host cells (such as macrophages, lymphocytes, endothelial cells, etc.…”
Section: Discussionmentioning
confidence: 99%